Effectiveness of the Marine Terminal Safety Inspector (MTSI) in Improving Ship Safety During Berthing (A Case Study at Pertamina Integrated Terminal Tanjung Uban Jetty) - Wahyu Wijayanto; Muhammad Firzah (Journal Research of Social Science, Economics, and Management, 2025)
Indonesia, as an archipelagic country, relies heavily on maritime distribution, especially for oil and gas, making ship safety during anchorage critical. PT Pertamina Integrated Terminal Tanjung Uban has implemented the Marine Terminal Safety Inspector (MTSI) program to enhance safety supervision based on international standards. However, the program’s effectiveness has not been thoroughly evaluated. This study investigates the effectiveness of the MTSI program in improving ship safety during berthing at the terminal. The MTSI program aligns with standards such as ISGOTT and IMO, replacing previous inspections by non-specialist personnel often marked by suboptimal supervision. It aims to ensure stricter, more professional inspections conducted by experienced inspectors. Using a qualitative descriptive approach, data were gathered from in-depth interviews with six key informants, each having over ten years of experience in terminal operations and safety inspections. Thematic analysis supported by the Fishbone diagram identified root causes of existing challenges. Findings reveal that while MTSI has increased regulatory compliance and risk awareness, issues persist, including inefficient resource allocation, limited digital innovation, poor inter-unit communication, and a lack of adaptive performance evaluation. To address these challenges, the study recommends improving competency-based training, digitizing inspections, creating cross-functional safety teams, and implementing adaptive performance indicators. These measures aim to enhance the sustainability and overall effectiveness of the MTSI program, contributing to safer berthing operations at Pertamina Integrated Terminal Tanjung Uban.